Regulatory utility of physiologically‐based pharmacokinetic modeling to support alternative bioequivalence approaches and risk assessment: A workshop summary report - Fang Wu; Youssef Mousa; Kimberly Raines; Chris Bode; Yu Chung Tsang; Rodrigo Cristofoletti; Hongling Zhang; Tycho Heimbach; Lanyan Fang; Filippos Kesisoglou; Amitava Mitra; James Polli; et al. (CPT: Pharmacometrics & Systems Pharmacology, 2023)
Abstract This report summarizes the proceedings for day 2 sessions 1 and 3 of the 2‐day public workshop entitled “Regulatory Utility of Mechanistic Modeling to Support Alternative Bioequivalence Approaches,” a jointly sponsored workshop by the US Food and Drug Administration (FDA) and the Center for Research on Complex Generics (CRCG). The aims of this workshop were: (1) to discuss how mechanistic modeling, including physiologically‐based pharmacokinetic (PBPK) modeling and simulation, can support product development, and regulatory submissions; (2) to share the current state of mechanistic modeling for bioequivalence (BE) assessment through case studies; (3) to establish a consensus on best practices for using PBPK modeling for BE assessment to help drive further investment by the generic drug industry into mechanistic modeling and simulation; and (4) to introduce the concept of a Model Master File to improve model‐sharing. The theme of day 2 covered PBPK absorption model for oral products as an alternative BE approach and a tool for supporting risk assessment and biowaiver (session 1), oral PBPK for evaluating the impact of food on BE (session 2), successful cases, and challenges for oral PBPK (session 3). This report summarizes the topics of the presentations of day 2 sessions 1 and session 3 from FDA, academia, and pharmaceutical industry, including the current status of oral PBPK, case examples as well as the challenges and opportunities in this area. In addition, panel discussions on the utility of oral PBPK in both new drugs and generic drugs from regulatory and industry perspective are also summarized.